THE EFFECT OF DISCLOSURE OF SUSTAINABILITY REPORTS AND CORPORATE GOVERNANCE ON THE FINANCIAL PERFORMANCE OF COMPANIES IN THE ASEAN REGION - Indra Faisal Rizki Mufid; Bandi Bandi (SEAN Institute, 2023)
The paradigm of good company performance can be measured based on the entity's ability to generate profits or profits in financial statements. This study uses secondary data, namely data obtained indirectly from the object of study sourced from the ASEAN regional company's financial report data base available at the ASEAN Capital Markets Forum (ACMF) data center. The results of this study also show that there is a positive influence between financial performance and sustainability reporting. This is indicated by a significance value of 0. 015 < 0.05, as well as a coefficient value of 0.579 which means that there is a positive influence. Based on the results of the test and discussion, it was concluded that the financial performance of entities in the ASEAN region has differences as well as good corporate governance.